Predictive Model of the Dropout Intention of Learners in Public High Schools in Valenzuela City - Loayon, Jayson (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study developed a predictive model of dropout intention among public junior high school learners in Valenzuela City by examining demographic characteristics, dropout-related factor domains, and selected dropout-related risk indicators. Anchored on the Theory of Planned Behavior, the study conceptualized dropout intention as an early indicator of potential school withdrawal and a basis for preventive intervention. A quantitative correlational-predictive research design was employed involving 4,653 Grades 7–10 learners enrolled in public secondary schools in Valenzuela City during School Year 2025–2026. Data were gathered using the researcher-developed Dropout Intention Assessment Questionnaire (DIAQ) and analyzed through descriptive statistics, Spearman’s Rank-Order Correlation, and Multinomial Logistic Regression. Results showed that Family Strain was the most prominent dropout-related factor, while Environmental Factors, Academic Burnout, and Negative School Pressure were present at moderate levels. Most learners demonstrated very low dropout intention, although a small proportion exhibited moderate to very high levels, indicating vulnerability to disengagement. Correlation analysis revealed that all dropout-related factor domains were significantly and positively associated with dropout intention. Multinomial logistic regression identified Academic Burnout as the strongest and most consistent predictor, followed by Family Strain, Negative School Pressure, grade retention, chronic absenteeism, academic failure, working student status, bullying experience, health-related absenteeism, and low parental educational attainment. The final model significantly improved predictive accuracy and demonstrated acceptable explanatory power for classifying learners according to dropout intention levels. The findings indicate that dropout intention is influenced by multiple interacting academic, family, school, and personal factors and that predictive analytics can support early identification and intervention efforts for learners at risk. The study aligns with Sustainable Development Goal (SDG) 4 on Quality Education and SDG 10 on Reduced Inequalities by promoting learner retention, educational continuity, and equitable access to educational opportunities. Its sustainability contribution lies in strengthening educational, institutional, and socio-economic sustainability through evidence-based learner support and data-informed dropout prevention initiatives.